2000
DOI: 10.2307/253680
|View full text |Cite
|
Sign up to set email alerts
|

Liquidity, Estate Liquidation, Charitable Motives, and Life Insurance Demand by Retired Singles

Abstract: In this article, a model of life insurance holding is formulated. It takes into account the liquidation values and liquidity of estate assets and the ability of life insurance death benefits to bypass the probate process. Tobit regressions based on the model are run using the U.S. Survey of Consumer Finances 1989 data set. The results showed net worth (fixing net liquid assets and annuity wealth) and annuity wealth (fixing net liquid assets and net worth) to be positively related to life insurance holding. Mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 28 publications
1
47
2
Order By: Relevance
“…Hau (2000) finds that the liquidity of asset holdings is significantly related to the life insurance holding decision. We therefore include in our models a measure of asset liquidity, calculated as the sum of liquid assets scaled by total assets (Liquidity).…”
Section: Control Variablesmentioning
confidence: 99%
“…Hau (2000) finds that the liquidity of asset holdings is significantly related to the life insurance holding decision. We therefore include in our models a measure of asset liquidity, calculated as the sum of liquid assets scaled by total assets (Liquidity).…”
Section: Control Variablesmentioning
confidence: 99%
“…Certain studies (Anderson & Nevin, 1975;Auerbach & Kotlikoff, 1989;Duker, 1969) found negative relationship between life insurance and level of education suggesting that more people involvement in gaining higher education reduces labour force affecting GDP of that country. There are studies that found insignificant relationship between life insurance and education or schooling as argued that insurance education is not basically provided at schools (Beck & Webb, 2003;Hau, 2000;Li et al, 2007;Ofoghi & Farsangi, 2013;Treerattanapun, 2011). And they also stated that educated people having insurance knowledge are more risk averse than without that knowledge.…”
Section: Hypothesis Iii-bmentioning
confidence: 99%
“…Still, the result must be interpreted with care, due to the strong correlation between schooling and GDP per capita. Hau (2000) analysed 3,143 households from US Survey of Consumer Finances (SCF), and stated that it is unclear if education affects life insurance. Treerattanapun (2011) suggested that tertiary education is not a good proxy for the capacity of a person to understand the complexity of insurance products because the knowledge of these products may not be taught in schools.…”
Section: Literature Reviewmentioning
confidence: 99%